THE EDUCATIONAL PROCESS ORGANIZATION IN KNRTUKAI: TRADITIONS AND NEW APPROACHES - Nikolay N. Malivanov; Dmitriy P. Danilaev (Высшее образование в России, 2017)
Abstract. The article focuses on the features of the educational process organization in KNRTUBKAI. The problems and the various aspects of the organization contradictions are highlighted. The paper shows the effectiveness of the integrated approach to the educational process implemented at KNRTUBKAI. On each level and stage of educational process there are applied special methods of technical specialists training process organization and management, in accordance with the concrete purposes of education stages. The organizational structure of interaction between students, companies and universities taking into account the dynamic conditions of their functioning is developed. The organizational structure defines the mechanisms of functioning – the rules and the procedures that govern joint activities and actions of each subject: enterprises, universities and students. The proposed approach does not make restrictions on the choice of the form of interaction, methodology and training aids.